Spatio-Temporal Climate Change Risk Assessment: Mangaung Metropolitan Municipality, South Africa - Hlalele, Bernard M. (Ecology, Environment and Conservation, 2019)
Scientists have warned about global warming, resulting in climate change risks such as droughts. In 2015, the Free State provincial government declared a state of drought risk disaster which was extended into 2016. The current study aimed to (i) assess the climate change risk on annual and seasonal temporal scales over all areas of the Mangaung Metropolitan Municipality, (ii) determine most-at-risk areas and (iii) advise government authorities /risk disaster management stakeholders about disaster risk reduction projects aimed at resilience and capacity building against adverse effects of climate risk disasters. Ten climate change vulnerability variables were collected from Stats SA, census, 2011. The study applied principal component analysis to determine the key variables that give rise to the existing vulnerability conditions in the study area. A 43 year long time series data set (1973- 2016) was also collected from an online source for RDI computation. The results show that some of the main underlying variables behind high vulnerability in this municipality are; number of people with no income, the young (0-14) and the elderly (65+), as identified by principal component analysis. The main towns seem to be less vulnerable compared to the rest of the other areas under study. The most vulnerable areas are in the outskirts of Thaba Nchu. Furthermore, climatic hazard analysis using RDI showed constant hazard severity and probability over a 43 year long time series data set on annual basis. To further assess climate change, RDI was computed on seasonal time scales which also showed no significant differences in both severity and probability. Due to the fact that the study used only one station over Mangaung Metropolitan Municipality to assess climate change conditions, the risk assessment analysis differences were influenced by differences in the vulnerability levels. High risk levels are therefore in the rural areas. The study recommends that the government and all relevant stakeholders set up income generating projects through which young people will not necessarily seek jobs in urban areas and help afford higher education costs.
Published Article
Keywords: Climate Change Risk; Disaster; Reconnaissance Drought Index; Temporospatial; Vulnerability